Pembuatan Sistem Informasi Nilai Raport Berbasis Website di SMP Negeri 7 Surakarta - ., Hermanto; Nuryna, Ayu Fiska; ., Haryani (APMMI - Asosiasi Profesi Multimedia Indonesia, 2009)
In the end of semester general test, the class guardian will have very heavy duties, one of which is to fill in the report mark. This work is the peak of class guardian’s work, in which the marks obtained from the subject teachers will be collected and then put into the report preparation formula and finally will become the students’ report value. It, of course, is not an easy task because this work requires precision, thoroughness and correct calculation. This research is based on the problems emerging: How to put the mark easily into the lager or manual report with calculator aids in summing or calculating the mark means? How to establish a report assessment system in SMP Negeri 7 Surakarta. The methods employed in this research were observation, literary study, interview, website designing, programming, trial, system implementation, and to implement the finished product from the website development into the internet network. Information is a data collection that is processed into the more useful and beneficial form to the recipient. Without information, a system will not run smoothly and finally it can die (Andri Kristanto 2003:6). In the system analysis stage, an aid is required, that is flowchart. Using the flowchart will facilitate the analysis of problem existing. The report mark information system is received and operated by the class guardian so that it will reduce the class guardian burden in putting the mark into the report. The application software used in the website preparation is Macromedia MX with PHP programming language and with MySQL database.